PERAN KOMUNIKASI INTERPERSONAL DALAM MEDIASI PENGARUH DISIPLIN KERJA DAN KECERDASAN EMOSIONAL TERHADAP LOYALITAS KERJA KARYAWAN (Studi Kasus Pada Karyawan Sekolah Tinggi Ilmu Ekonomi Indonesia). - Marmin, Marmin; Sampurna, Dian Surya (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2025)
This research aims to analyze the role of interpersonal communication in mediating the influence of work discipline and emotional intelligence on employee work loyalty at the Indonesian College of Economics. The research method used was quantitative with a survey approach, using a questionnaire distributed to 86 respondents. Data analysis was carried out using the Structural Equation Modeling (SEM) method using SmartPLS 4 software. The research results showed that work discipline and emotional intelligence had a positive effect on interpersonal communication. Interpersonal communication is also proven to have a significant mediating role in the relationship between work discipline and emotional intelligence and employee work loyalty. These findings confirm that effective interpersonal communication can strengthen the relationship between these variables, thereby increasing employee loyalty to the organization.